Analisis Waktu Baku dan Kapasistas Produksi dalam Proses Pembuatan Mesin Perontok Jagung di CV. Citra Dragon - Agung Priatama; Rozza Linda; Mufrida Meri Z; Juwita Isna (Politeknik ATI Padang, 2021)
This study aims to calculate the standard time to produce the right time in producing corn thresher machine, so that the production capacity in one month is obtained at CV. Citra Dragon. Observations was made in the manufacture of corn threshing machine. Working time data was collected using stopwactch time study and adjustment method used was Westinghouse. The research method use was to analyze the work done by operators in the manufacture of corn thresher machine, and calculate the operator’s working time per work element. The result showed that the standard time needed in the process of making 1 unit of corn thresher machine is 78.603 second (21 hours) and the production capacity per month is 7 units of corn thresher machine.